2023
DOI: 10.1109/jsen.2022.3195274
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition Using Self-Powered Sensors Based on Multilayer Bidirectional Long Short-Term Memory Networks

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Channel state information (CSI) provides information about the amplitude and phase of the transmitted signals so that we can be aware of changes in Wi-Fi signals, including signal scattering, ambient attenuation, environmental fading (including multipath fading and shadow fading), and power decays because of distance in each transmission path during propagation [ 21 ]. Using CSI in this context instead of RSSI has many advantages, including more sustainability, reduced environmental influences, and increased transmission of information [ 3 , 22 ]. In addition, OFDM technology can be used in Wi-Fi devices, and the bandwidth can be divided between several orthogonal subcarriers by using the IEEE 802.11 n/ac standard.…”
Section: System Methodsmentioning
confidence: 99%
“…Channel state information (CSI) provides information about the amplitude and phase of the transmitted signals so that we can be aware of changes in Wi-Fi signals, including signal scattering, ambient attenuation, environmental fading (including multipath fading and shadow fading), and power decays because of distance in each transmission path during propagation [ 21 ]. Using CSI in this context instead of RSSI has many advantages, including more sustainability, reduced environmental influences, and increased transmission of information [ 3 , 22 ]. In addition, OFDM technology can be used in Wi-Fi devices, and the bandwidth can be divided between several orthogonal subcarriers by using the IEEE 802.11 n/ac standard.…”
Section: System Methodsmentioning
confidence: 99%
“…Compared with the above methods, several studies [22][23][24][25] have shown that WiFibased human action recognition has been favored by many researchers in recent years due to many advantages such as wide coverage, strong privacy protection, low price, the ability to detect non-visual distance, and no need to wear or touch. The WiFi-based human action recognition mainly relies on two signals: (1) the received signal strength indicator (RSSI); and (2) channel state information (CSI).…”
Section: Introductionmentioning
confidence: 99%
“…The paper [8] proposed a fall detection system WiFall to achieve an accuracy of 87% of users' fall detection. The paper [9] proposes an activity recognition model based on a three-layer bidirectional long-and short-term memory network fused with attention to classify and recognize six activities in the open dataset in the paper [10] , and the experimental results show that the recognition rate can reach 96%. The paper [11] proposed an attentional temporal convolutional network by extracting continuous CSI time-domain features, and verified its advanced recognition rate in multiple datasets.…”
Section: Introductionmentioning
confidence: 99%